"To Be, or Not to Be, That Is the Question"—The Cretan Extensional Detachment, Greece. Issue 9 (17th September 2018) - Ring, Uwe; Yngwe, Frej
Abstract: We present new structural data from the contact zone between the high‐pressure Phyllite‐Quartzite unit (PQ) and the overlying non‐high‐pressure Tripolitza unit in east‐central Crete for testing propositions that this contact represents the top‐to‐the‐north Cretan extensional detachment. Detailed mapping in the Neapoli valley shows that the PQ/Tripolitza contact is associated with a shallowly dipping penetrative foliation and associated south‐southwest (SSW)‐trending stretching lineation in the PQ. Kinematic indicators yielded a consistent top‐to‐the‐SSW sense of shear. The Tripolitza unit above was brittlely deformed, and top‐to‐the‐SSW thrust faults sole out in the contact zone. Undoing the effects of subsequent large‐wavelength, low‐amplitude folding about west‐northwest‐trending axes of the contact indicates that the top‐to‐the‐SSW kinematics resulted from crustal shortening. Therefore, the PQ/Tripolitza contact in the Neapoli valley is an out‐of‐sequence thrust, the Tripolitza thrust. We discuss a tectonic model in which the high‐pressure PQ was first exhumed in a shortening‐related extrusion wedge between about 22 and 17 Ma. The top of the exhuming extrusion wedge was then cut off by out‐of‐sequence thrusts in the upper crust at ≥17–11 Ma during sustained N‐S shortening. Subsequently, extensional graben in Crete formed after 11 Ma. Plain Language Summary: The Aegean Sea basin is a superb example of large‐scale horizontal extension in the overriding plate above a subduction zone. A matter of debate is how much this extensional deformation aided the return of once deep‐seated rocks back to the Earth's surface. On the island of Crete, the alleged Cretan detachment has been proposed to be a large‐scale extensional structure. However, several colleagues came to very different conclusions. We decided to help in answering the question of whether or not the Cretan detachment is a shortening or extensional structure by conducting a detailed field study along a well exposed and structurally simple segment of the Cretan detachment. Our results show that the proposed Cretan extensional detachment is actually a shortening structure. Key Points: Our detailed structural mapping shows that the alleged Cretan extensional detachment is an out‐of‐sequence thrust There was sustained N‐S shortening during the exhumation of the Cretan high‐pressure rocks North‐south directed extensional deformation in Crete did not commence before 11 Ma